Collection, conservation and evaluation of priority indigenous vegetables in Sri Lanka - Jeewani, D.G.C.; Balasooriya, B.G.R.C.; Kondasinghe, K.M.C.L.; Danwatta, A.S.J.; Hunter, Danny; Borelli, Teresa (2024)
A diverse range of underutilized vegetables and leafy greens in Sri Lanka were identified for collection, conservation, and genetic improvement. Within the framework of the CGIAR Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) in Sri Lanka, in 2023 the Plant Genetic Resources Centre, Sri Lanka (PGRC) prioritized ten crops for exploration, characterization and ex situ conservation. The list included vegetables such as sword bean, sponge gourd, snake gourd, winged bean and moringa, as well as leafy greens such as Amaranthus spp., fame flower, balloon plant, sickle pod and vegetable hummingbird.